2014
DOI: 10.1016/j.actbio.2014.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac differentiation of cardiosphere-derived cells in scaffolds mimicking morphology of the cardiac extracellular matrix

Abstract: Stem cell therapy has the potential to regenerate heart tissue after myocardial infarction (MI). The regeneration is dependent upon cardiac differentiation of the delivered stem cells. We hypothesized that timing of the stem cell delivery determines the extent of cardiac differentiation as cell differentiation is dependent on matrix properties such as biomechanics, structure and morphology, and these properties in cardiac extracellular matrix (ECM) continuously vary with time after MI. In order to elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Following gelation at 37°C for 20 min, cell culture medium was added. After 1, 7, and 14 days of culture under normal tissue culture conditions (20% O 2 and 5% CO 2 ), dsDNA (for live cells) content in the hydrogels was measured by PicoGreen assay kit (Invitrogen) following the protocol reported previously [52].…”
Section: Mscs Encapsulation In Hydrogelsmentioning
confidence: 99%
“…Following gelation at 37°C for 20 min, cell culture medium was added. After 1, 7, and 14 days of culture under normal tissue culture conditions (20% O 2 and 5% CO 2 ), dsDNA (for live cells) content in the hydrogels was measured by PicoGreen assay kit (Invitrogen) following the protocol reported previously [52].…”
Section: Mscs Encapsulation In Hydrogelsmentioning
confidence: 99%
“…We have demonstrated that CDCs differentiated into cardiomyocytes in fibrous scaffold based on poly(ester urethane)urea and PNIPAAm hydrogel, and the most significant differentiation was in scaffold with elastic modulus of ~50–60 kPa. 62 Besides CDCs, other cell types also showed matrix modulus-driven cardiac differentiation. MSCs had the highest cardiac differentiation in 65 kPa hydrogel based on NIPAAm, N -acryloxysuccinimide, AAc, and poly(trimethylene carbonate)-hydroxyethyl methacrylate.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, biosimulation of cardiac microenvironment into the scaffolds is an important matter to determine the output of heart tissue engineering. Specifically, all of the cardiac microenvironment components including growth factors [Lin et al, ; Lisi et al, ], decellularized tissue matrices [Xu et al, ] and synthetic polymer scaffolds [Parrag et al, ; Crowder et al, ] are as key matters to achieve the effective injured heart masculinization and revascularization. Moreover, preserving the survival and function of the seeded cell against the low oxygen and nutrient condition [Kawamura et al, ] is a crucial feature for heart tissue engineering efficiency which it has a close relationship with biosimulation of the cardiac microenvironment.…”
Section: Cell Therapymentioning
confidence: 99%